The Pandemic Pregnancy: Canadian Maternity Experiences During the COVID-19 Pandemic - Shaw, Sigourney (Université d'Ottawa / University of Ottawa, 2023)
The purpose of this thesis is to investigate how a public health crisis affects the pregnancy decisions and experiences of Canadians, how pregnancy history impacts these experiences, and whether the delivery of pregnancy care has been impacted or changed by the COVID-19 pandemic. This thesis surveyed women from across the country about their experiences during pregnancy with prenatal care and social support, as well as their birth experiences and perceptions of new motherhood during the pandemic. Interviews were conducted with perinatal care providers from Ontario about their personal experiences providing perinatal healthcare services, as well as their perceptions of their patients’ experiences. This thesis aims to identify prenatal, birth and postpartum experiences described by Canadians, and quality of perinatal health services during the COVID-19 pandemic.
Keywords: Pregnancy; Maternal Health; Pandemic; COVID-19; Maternity Care; Reproductive Health